Analisis Penerapan PSAK No. 65 Pada Penyusunan Laporan Keuangan Toko Cabang XYZ - Junidar Lorensia Telaumbanua; Suci Pajriana; Tio Sinta Marito Br. Marbun; Zahra Adinda (Jurnal Akuntansi Keuangan dan Bisnis, 2025)
This article discusses the application of Statement of Financial Accounting Standards (PSAK) No. 65, which regulates Consolidated Financial Statements, in the preparation of the financial statements of XYZ Branch Store. PSAK 65 emphasizes the importance of presenting consolidated financial statements for parent entities that have control over subsidiaries, including branches with separate legal entities. The purpose of this study is to observe how the application of this PSAK affects the recording, measurement, presentation, and disclosure of financial transactions at the branch, while also assessing XYZ Branch Store's compliance and its impact on the relevance of its financial statements. This study uses a qualitative approach with a case study method and data collection techniques through interviews and direct observation. The results show that XYZ Branch Store still uses a simple cash-based accounting method and prepares internal financial reports covering income, expenses, accounts payable, and receivables. Furthermore, the inventory management system is still monitored and controlled by the head office, which is in line with the proper implementation of PSAK 65.